Family Disruption as a New Prospect to Consider in Traumatic Brain Injury - Rijal, Suman; Nepal, Pankaj Raj (Eastern Green Neurosurgery, 2020)
Background: Different types of behavioral changes are seen in head injury patients, and these changes are directly or indirectly related to the daily activities of both patient and the family members. The impact of head injury has affected the relationships in the family and friendship status too. Even it has brought about divorce and other family disruption in the present modern world. This study was designed with the aim of evaluating family disruption in different grades of head injury. Materials and methods: This is a prospective analytical study that included 76 patients with non-probability consecutive sampling conducted at the National Institute of Neurological and Allied Sciences, Bansbari, Nepal over 6 months duration. All head-injured patients above the age of 16 years were included and patients with Extended Glasgow Outcome Scale of less than 3 at 6 months follow up were excluded. Their age, gender, mode of injury, GCS at presentation were collected. Extended Glasgow Outcome Scale and their family adjustment were evaluated at 6 months. The family adjustment was seen and analyzed from the GOS-E interview questionnaire. Data analysis was done using SPSS v.20. Results: The total number of patients was 76 among which 71% were below 40 years of age and the majority (87%) were males. The commonest mode of injury was a road traffic accident (35, 46%) followed by injury due to fall and physical assault. Of all, 76% (58/76) were mild head injured followed by 15% (11/76) severe head-injured patients. At 6 months, the Extended Glasgow Outcome Scale (EGOS) of 7 and 8 were obtained in 37% and 43% of the patients respectively. All the family who had severe head-injured patients and about 85% of the family with moderate head-injured patients had a significant degree of family disruption. Also, 8% of families with Mild head-injured patients had some degree of family disruption. Family disruption and its extent of severity were significantly related to the severity of the head injury. Conclusion: Family disruption and extent of disruption/ strain are also strongly associated with the severity of the head injury.